Mental Health Issues in Higher Education: Increasing Awareness, Access to Therapy, and Campus Support - Darmawati. R; Septin Maisharah K; Muhammad Umer Farooq Mujahid (Westscience Press, 2023)
This study investigated the state of mental health among students at a leading university in West Java, Indonesia, focusing on the prevalence of mental health problems, awareness of available resources, access to therapy, and the effectiveness of campus support systems. A quantitative approach was employed, using a cross-sectional survey to collect data from a representative sample of 200 students. The results showed a significant prevalence of mental health challenges, including stress, anxiety, and depressive symptoms. Worryingly, most students lacked awareness of available mental health resources. Access to therapy and counseling services is hindered by stigma and long wait times. While some campus support systems received positive feedback, others were deemed in need of improvement. To address these issues, recommendations included a comprehensive awareness campaign, efforts to reduce stigma, increased access to counseling services, and improved campus support systems. These findings underscore the urgent need to prioritize mental health support within the university community.